7(t-6)+5t=4(3t+5)-12

Simple and best practice solution for 7(t-6)+5t=4(3t+5)-12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(t-6)+5t=4(3t+5)-12 equation:


Simplifying
7(t + -6) + 5t = 4(3t + 5) + -12

Reorder the terms:
7(-6 + t) + 5t = 4(3t + 5) + -12
(-6 * 7 + t * 7) + 5t = 4(3t + 5) + -12
(-42 + 7t) + 5t = 4(3t + 5) + -12

Combine like terms: 7t + 5t = 12t
-42 + 12t = 4(3t + 5) + -12

Reorder the terms:
-42 + 12t = 4(5 + 3t) + -12
-42 + 12t = (5 * 4 + 3t * 4) + -12
-42 + 12t = (20 + 12t) + -12

Reorder the terms:
-42 + 12t = 20 + -12 + 12t

Combine like terms: 20 + -12 = 8
-42 + 12t = 8 + 12t

Add '-12t' to each side of the equation.
-42 + 12t + -12t = 8 + 12t + -12t

Combine like terms: 12t + -12t = 0
-42 + 0 = 8 + 12t + -12t
-42 = 8 + 12t + -12t

Combine like terms: 12t + -12t = 0
-42 = 8 + 0
-42 = 8

Solving
-42 = 8

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 6r+2=46r+10 | | 5/3x-7/5=-1/3x-1 | | x(x^2-8)=0 | | 5.9+1.6n=2.54 | | 4(v+7)=-4(4v-9)+4v | | 3a=c-a(b+a) | | (24x-1)=(x+1)(x+2)(4) | | 9y=y+8y | | -5m-5=0 | | 1+5r=11-5r+8r | | 12/5z=7/3 | | 25=2c-19 | | y-5x+3=0 | | (ln(x))/(x/2) | | 2x^(2/3)-19x^(1/3)-14=0 | | kx^2-9x+4k+1=0 | | 8m-1=-9+1+7m+2 | | x+3-4=x+5 | | 5-5m=0 | | Cos(pi/6t) | | y=0.5(h+8)3 | | 3(5x-8/6)-3=18 | | -7b+28= | | 10y^2+12y-144=0 | | 12-6h=18 | | 2p-4=-10 | | 7b+28= | | 0.06x+0.14(50000-x)=4500 | | 5(x-4)+3x=8+2x | | .4x+.4y=-23.2 | | -x+(-1/4x)+(-7/16x)=-131/2 | | -5+8-(-3x)-6=22 |

Equations solver categories